Higher temperatures are associated with reduced nestling body condition in a range‐restricted mountain bird. (4th July 2021) - Oswald, Krista N.; Smit, Ben; Lee, Alan T. K.; Peng, Ceili L.; Brock, Cameryn; Cunningham, Susan J.
Abstract : Demonstrated negative effects of increased temperatures on avian reproductive success suggest a mechanism by which climate change may impact species persistence. High temperatures can result in reduced parental care and reduced nestling condition in passerines with dependent young, resulting in lowered fledging success and population recruitment. We examined provisioning rate and nestling condition in a South African mountain endemic, the Cape rockjumper Chaetops frenatus, whose population declines correlate with warming habitat. Our aim was to determine whether rockjumper reproductive success could be affected by high air temperatures. We set up video cameras on nests at three nestling age classes (≤ 7 days old; 8–12 days old; ≥ 13 days old) for 8 hours on 37 separate days. We successfully collected full‐day footage on 25 of the 37 days (four days with predation, eight with equipment failure). Nestlings were weighed at the beginning and end of each film day, barring the four days with mid‐day predation (n = 65 nestling measures from 33 of the 37 days). Average mass gain across all nestlings per nest was positively correlated with provisioning rate (0.78 g provisions −1 hr −1, CI: 0.26–1.30), and provisioning rate decreased at increasing temperatures (−0.08 provisions hr −1 °C −1, CI: −0.15 to −0.01). Daily change in mass of individual nestlings was negatively correlated with air temperatures above a significant temperature threshold (22.4°C; −0.30 g °C −1, CI: −0.40 to −0.19). This suggests nestling energy requirements were not being met on higher temperature days – perhaps because nestling energy and water demands for thermoregulation are elevated and provisioning rate is not correspondingly maintained or increased. These results suggest that higher temperatures negatively affect nestling mass gain. While in our study this did not directly affect fledging rates, it may affect post‐fledging survival.